CD45RO and CD45RA positive cell populations in idiopathic membranous and IgA glomerulopathy. Issue 1 (January 1996) - Lee, A H; Bass, P S; Williams, J H; Evans, B; Jones, D B; Theaker, J M; Davies, D R
Abstract : AIMS: To immunophenotype and quantitate glomerular and interstitial inflammatory cells in cases of idiopathic membranous and IgA glomerulopathy; to correlate cell numbers with aspects of clinical data and renal function. METHODS: Routine indirect immunoperoxidase staining was performed on frozen section renal biopsy specimens for T and B lymphocyte related antigens, macrophages and MHC class II antigens. Double immunohistochemical staining was performed to identify CD45RO+ and CD45RA+ cells. RESULTS: In IgA glomerulopathy correlations were found relating interstitial cell numbers to creatinine concentration at biopsy (CD45RO+ and CD45RA+ cells) and follow up creatinine concentration (CD3+, CD4+, CD8+, CD45RO+, and CD45RA+ cells). Also in IgA glomerulopathy mean arterial pressure at biopsy correlated with interstitial cell numbers and most recent follow up creatinine concentration. There were no correlations between glomerular inflammatory cells and renal function in either disease. Double staining showed that although most glomerular CD45RO+ and CD45RA+ cells were macrophages, positive cells in the interstitium were lymphocytes. The interstitial CD45RO+:RA+ ratio in normal renal biopsy specimens was approximately 5:1; for IgA glomerulopathy it was 1.5 and was 1.0 in idiopathic membranous glomerulopathy. CONCLUSIONS: This study demonstrates that interstitial, and not glomerular, inflammatory cell numbers correlate with renal function in primary glomerular disease and that double staining is necessary to interpret positive immunostaining for antigens located on more than one type of inflammatory cell. Detailed investigation of the interstitial CD45RO+ and CD45RA+ cells may give an insight into the pathogenesis of glomerular disease.